The concept of climate diplomacy in modern scientific discourse - Tykhomyrova, Yevhenya B. (ScientificWorld-NetAkhatAVKarlsruhe, 2022)
The chapter is devoted to the problem of global climate change. The recognition of the need to solve this problem has determined the importance of professional diplomats’ participation in this process. Consequently, this gave rise to the problem of climate diplomacy which emergence is associated with the second half of the 20th century. The author attempts to develop a relevant theory that integrates with the management of international relations / foreign policy. That is why the conceptualization of climate diplomacy takes place in the context of international political problems. The analysis of the studies has revealed the dearth of works in the domestic scientific tradition aimed at researching the problem of climate diplomacy. Climate diplomacy is considered in the context of traditional, classical diplomacy. The presented chapter explores the following issues: climate diplomacy essential characteristics, main elements and features of climate diplomacy, climate diplomacy communication strategy and the main directions of the EU climate diplomacy.
Keywords: Global climate change; international relations; classical diplomacy; climate diplomacy; communication strategy of climate diplomacy